2020
DOI: 10.1144/petgeo2020-005
|View full text |Cite
|
Sign up to set email alerts
|

The influence of inter- and intra-channel architecture on deep-water turbidite reservoir performance

Abstract: Bed-scale heterogeneity in channelized deep-water reservoirs can significantly influence reservoir performance, but reservoir simulation typically requires cell sizes much greater than the scale of intra-channel element architecture. Here, bed- to geobody-scale simulations elucidate the influence of bed-scale architecture and channel element stacking on flow and connectivity, informing full-field reservoir model development and evaluation.Models consist of two channel element segments, each 300 m (985 ft) wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…8B), where sandstones in the axis truly are connected, as suggested by many reservoir models (e.g., Alpak et al, 2013) and demonstrated in some subsurface production data (Gonzalez-Carballo et al, 2006). However, MTDs within channel elements (e.g., Bernhardt et al, 2012;Ortiz-Karpf et al, 2015) and the vertical stacking of migrating elements can drastically impact the overall connectivity of a submarine channel complex (Jackson et al, 2019;Meirovitz et al, 2021).…”
Section: Facies Continuity In Dip Versus Strike Viewmentioning
confidence: 89%
See 1 more Smart Citation
“…8B), where sandstones in the axis truly are connected, as suggested by many reservoir models (e.g., Alpak et al, 2013) and demonstrated in some subsurface production data (Gonzalez-Carballo et al, 2006). However, MTDs within channel elements (e.g., Bernhardt et al, 2012;Ortiz-Karpf et al, 2015) and the vertical stacking of migrating elements can drastically impact the overall connectivity of a submarine channel complex (Jackson et al, 2019;Meirovitz et al, 2021).…”
Section: Facies Continuity In Dip Versus Strike Viewmentioning
confidence: 89%
“…Of particular importance is the surface and facies architecture near the edges of channel deposits, where thick-bedded amalgamated sandstones transition to thinly-bedded sandstone-mudstone couplets (Mutti & Normark, 1987). The detailed 3D architecture at this transition strongly affects reservoir connectivity within and between channel deposits (e.g., Alpak et al, 2013;Jackson et al, 2019;McHargue et al, 2011;Meirovitz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies in similar reservoirs [129][130][131] showed that facies architecture in channel systems has a negative impact on recovery. Various techniques have been proposed to enhance production [129,132]. Concerning post-deposition effects on reservoir quality, especially the impact of tectonics, NW-SE-trending reverse faults may result in the confinement of channel fairways that, in many cases, have the same orientation in the study area.…”
Section: Reservoir Evaluationmentioning
confidence: 99%
“…Interpretation and reconstruction of AMRs plays an important part in identifying palaeo-environment and palaeoclimate (Foreman & Straub, 2017;Hazelwood & Stetler, 2019;Ielpi & Lapôtre, 2019;Morecroft et al, 2019;Yang et al, 2020) and is also a significant component of hydrocarbon exploration and exploitation (Lin et al, 2018a(Lin et al, , 2018bMu et al, 2015;Parquer et al, 2020;Shan et al, 2015a;Willis et al, 2015;Wu et al, 2012;Yue et al, 2007). However, due to the extremely complex characteristics of hydrocarbon reservoir architecture (Fustic et al, 2019;Meirovitz et al, 2016;Qiao et al, 2019;Ru et al, 2016;Singh et al, 2016), limited underground data (Shan et al, 2015c) and diversity of channel-bend transformations (i.e. expansion, translation, rotation or a combination thereof) (Chen et al, 2017;Ghinassi et al, 2014;Hooke et al, 2011;Ielpi & Ghinassi, 2014;Johnston & Holbrook, 2018;Lin et al, 2017;Seminara, 2006), reconstruction of the evolutionary process of AMRs is a major challenge (Willis & Sech, 2018a).…”
Section: Introductionmentioning
confidence: 99%